2013
DOI: 10.4055/cios.2013.5.4.278
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Preservation is Helpful to Obtain Good Clinical Results in Posterior Cruciate Ligament Reconstruction: Comparison of Clinical Results of Three Techniques

Abstract: BackgroundThe purpose of the present study was to compare the clinical results of 3 posterior cruciate ligament reconstruction techniques according to the time from injury to surgery and remnant PCL status and to evaluate the efficiency of each technique.MethodsThe records of 89 patients who underwent primary PCL reconstructions with a posterolateral corner sling were analyzed retrospectively. Thirty-four patients were treated by anterolateral bundle (ALB) reconstruction with preservation of the remnant PCL us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…29,30 There were many studies that reported the outcomes of PCLR that included patients with posterolateral corner (PLC) injuries. 23,31,32 In PCLR the identification of concomitant injuries of the PLC is important for optimizing the surgical and clinical outcomes. We believed that the role of the PCL remnant would be clarified by comparing isolated PCLR with versus without remnant preservation.…”
Section: Remnant Preservationmentioning
confidence: 99%
“…29,30 There were many studies that reported the outcomes of PCLR that included patients with posterolateral corner (PLC) injuries. 23,31,32 In PCLR the identification of concomitant injuries of the PLC is important for optimizing the surgical and clinical outcomes. We believed that the role of the PCL remnant would be clarified by comparing isolated PCLR with versus without remnant preservation.…”
Section: Remnant Preservationmentioning
confidence: 99%
“…After reading the full texts of the remaining 22 articles, 15 were excluded owing to the absence of usable information regarding clinical and stability outcomes or because they were case series evaluating either the transtibial or tibial inlay technique without direct comparison of the two approaches. After applying these criteria, seven studies [9,13,15,[20][21][22][23] were finally included in this systematic review.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…This remnant preservation is advantageous to gain postoperative stability, restore proprioception by saving mechanoreceptors, and avoid the killer-turn effect by acting like a cushion. 2 , 7 , 8 , 9 , 10 , 11 If the remnant fibers of the PCL are removed to expose the bony landmark, we have to use at least a 10-mm-diameter graft for PCL reconstruction. However, in the remnant-preservation technique, we have tried to preserve the remnant fibers of the PCL as much as possible, and when performing this technique, we have been able to use a graft and tibial tunnel with an 8-mm diameter, on average, to augment and reinforce the remnant PCL bundles, especially for the anterolateral bundle.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 7 If the remnant PCL fibers are well preserved, this could contribute to knee stability, restoration of proprioception by saving mechanoreceptors, and prevention of the killer-turn effect. 2 , 3 , 7 , 8 , 9 , 10 , 11 …”
mentioning
confidence: 99%